Preparation, structural and optical characterization of BaWO4 and PbWO4 thin films prepared by a chemical route - Pontes, F. M.; Maurera, MAMA; Souza, A. G.; Longo, Elson [UNESP]; Leite, E. R.; Magnani, R.; Machado, MAC; Pizani, P. S.; Varela, José Arana [UNESP] (Elsevier B.V., 2003)
Polycrystalline BaWO4 and PbWO4 thin films having a tetragonal scheelite structure were prepared at different temperatures. Soluble precursors such as barium carbonate, lead acetate trihydrate and tungstic acid, as starting materials, were mixed in aqueous solution. The thin films were deposited on silicon, platinum-coated silicon and quartz substrates by means of the spinning technique. The surface morphology and crystal structure of the thin films were investigated using scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray diffraction, and specular reflectance infrared Fourier transform spectroscopy, respectively. Nucleation stages and surface morphology evolution of thin films on silicon substrates have been studied by atomic force microscopy. XRD characterization of these films showed that BaWO4 and PbWO4 phase crystallize at 500 degreesC from an inorganic amorphous phase. FTIR spectra revealed the complete decomposition of the organic ligands at 500 degreesC and the appearance of two sharp and intense bands between 1000 and 600 cm(-1) assigned to vibrations of the antisymmetric stretches resulting from the high crystallinity of both thin films. The optical properties were also studied. It was found that BaWO4 and PbWO4 thin films have Eg = 5.78 eV and 4.20 eV, respectively, of a direct transition nature. The excellent microstructural quality and chemical homogeneity results confirmed that soft solution processing provides an inexpensive and environmentally friendly route for the preparation of BaWO4 and PbWO4 thin films. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: BaWO4; PbWO4; polymeric precursors; thin films